Pelatihan Menyenangkan Menemukan dan Memahami Pesan Kitab Suci di Institut Agama Kristen Renatus Pematang Siantar - Pasaribu, James; Pardede, Marlan; Lubis, Terapul (Journal Of Human And Education (JAHE), 2024)
Finding the message and meaning of the Holy Book is the longing for the spirituality of every religious believer. In the realm of Theology, this field is called heme neurology (the science of interpretation). Interpreting activities start with reading and end with doing the message of the Word in daily life. Students of the Renatus Christian Religious Institute in Pematang Siantar have difficulty finding the message of God's Word, especially when it is connected to ministry activities in the Church. Preparing sermon material, whether it is for children (Sunday school) or youth, is a series of processes that start with finding the message of God's Word. This activity was carried out as one of the solutions for students so that the service place would have a passion for returning. Students are given training using the BGA method developed and taught by SU Indonesia. In this activity, a method of understanding the genre of Narrative and Psalm was given along with exercises and group percentages. The results showed the ability and accuracy in finding and interpreting the texts given in the group. Likewise, the percentage of group work results is conveyed in straightforward, easy-to-understand, and on target language. Participants hope that there will be similar activities in the future to equip them with the ability to find the message of God's Word in other genres.